Perspectives on Amplifying Participation in Museums Through Global Digital Citizenship - Ann Borda; Jonathan P. Bowen (Heritage)
In this paper, we consider the concept of global digital citizenship, particularly as it applies to museums and cultural heritage sectors. In this perspective survey study, we explore current examples of how museums can adjust to the tenets of global digital citizenship that are necessary to navigate and participate in increasingly interconnected digital worlds and to collectively address global challenges. This paper provides a qualitative survey and discussion covering issues concerning open foundations, knowledge co-creation, digital equity and inclusion, and participatory innovation. In conclusion, there are untapped opportunities for museums (e.g., through audience participation and digital tools, especially with recent developments in artificial intelligence), but also constraints that must be considered (e.g., lack of funding, digital inequality, and ethical issues related to the use of AI).